Effects of laser shock peening on the microstructure and fatigue crack propagation behaviour of thin AA2024 specimens. (May 2017) - Kashaev, Nikolai; Ventzke, Volker; Horstmann, Manfred; Chupakhin, Sergey; Riekehr, Stefan; Falck, Rielson; Maawad, Emad; Staron, Peter; Schell, Norbert; Huber, Norbert
Graphical abstract: Highlights: Deep compressive residual stresses introduced without severe surface damages. Significant FCP retardation observed due to compressive residual stresses. LSP compressive residual stresses caused crack closure effect. The crack closure effect increased opening load and reduced effective load range. A methodology to consider the LSP residual stresses for the FCP behaviour proposed. Abstract: Laser shock peening (LSP) was performed on aluminium alloy AA2024 with a thickness of 2.0 mm. Microstructural studies using the electron back scatter diffraction (EBSD) technique were performed to quantify the micro-texture changes in the material through LSP. A residual stress analysis was performed using synchrotron radiation and a hole drilling technique. Fatigue crack propagation (FCP) tests were performed to investigate the retardation effect of LSP residual stresses. Load versus crack opening displacement curves were analysed to obtain the corrected values of load opening levels considering the effects of the residual stresses. Specimens with the LSP treatment reveal a significant retardation of the FCP. The presence of compressive residual stresses caused the crack closure effect, which increased the level of crack opening load and therefore reduced the effective load range. An original methodology to consider LSP-induced residual stresses on the FCP behaviour was proposed.